2020
DOI: 10.48550/arxiv.2005.11784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The vanishing of the fundamental gap of convex domains in $\mathbb H^n$

Abstract: For the Laplace operator with Dirichlet boundary conditions on convex domains in H n , n ≥ 2, we prove that the product of the fundamental gap with the square of the diameter can be arbitrarily small for domains of any diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…To find an upper bound estimate for λ 2 , we will seek in the next section an upper bound for the first eigenvalue of a more general Schrödinger equation and, as such, we will simultaneously obtain an upper bound for λ 1 , slightly improve the one in (5).…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…To find an upper bound estimate for λ 2 , we will seek in the next section an upper bound for the first eigenvalue of a more general Schrödinger equation and, as such, we will simultaneously obtain an upper bound for λ 1 , slightly improve the one in (5).…”
Section: 2mentioning
confidence: 99%
“…In hyperbolic space, this quantity behaves very differently from the Euclidean and spherical cases. Recently, the authors showed [5] that for any fixed D > 0, there are convex domains with diameter D in H n , n ≥ 2, such that D 2 (λ 2 − λ 1 ) is arbitrarily small. Since convexity does not provide a lower bound, one naturally asks if imposing a stronger notion of convexity, such as horoconvexity, would imply an estimate for D 2 (λ 2 − λ 1 ) from below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Dai, He, Seto, Wang, and Wei (in various subsets) [4,6,9] generalized the estimate to convex domains in S n , showing that the same bound holds: λ 2 − λ 1 ≥ 3π 2 /D 2 . Very recently, the second author with coauthors [3] showed the surprising result that there is no lower bound on the fundamental gap of convex domain in the hyperbolic space with arbitrary fixed diameter. This is done by estimating the fundamental gap of some suitable convex thin strips.…”
Section: Introductionmentioning
confidence: 99%